2007
DOI: 10.1093/rheumatology/kem115
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the cost effectiveness of TNF-  antagonists in the management of rheumatoid arthritis: results from the British Society for Rheumatology Biologics Registry

Abstract: The BSRBR data provide valuable evidence for estimating cost-effectiveness. The analysis concludes that current policies and practice for the use of TNF-alpha antagonist therapies, after RA patients have failed at least two traditional disease-modifying anti-rheumatic drugs, appear cost-effective in the context of the NICE re-appraisal of 2006 for England and Wales, thus supporting their decision to continue their reimbursement. Decision-makers worldwide might adapt this analysis because differential costs, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
90
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 52 publications
0
90
0
2
Order By: Relevance
“…Data from Brennan et al 183 were used to estimate the number of hospitalisations within the UK for every cycle of the model dependent on a number of characteristics, including TNF-α inhibitor treatment, which is used as a proxy for bDMARD treatment. The coefficients reported in Brennan et al 183 are reproduced in Table 123.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Brennan et al 183 were used to estimate the number of hospitalisations within the UK for every cycle of the model dependent on a number of characteristics, including TNF-α inhibitor treatment, which is used as a proxy for bDMARD treatment. The coefficients reported in Brennan et al 183 are reproduced in Table 123.…”
mentioning
confidence: 99%
“…The coefficients reported in Brennan et al 183 are reproduced in Table 123. Costs of an inpatient day were estimated from NHS reference costs 2010-11 (non-elective inpatient PA34B) with a mean of £517.…”
mentioning
confidence: 99%
“…Eight studies (19%) reported significant uncertainty, [39,[45][46][47]49,55,65,73] with six studies (14%) reporting specific model parameters which lead to significant sensitivity in the economic model. These were: the baseline age in the model; [39] the standardised mortality ratios; [39] the algorithm to estimate health related quality of life;, [39,45,65] the rate of disease progression; [45,46] discount rates; [45] treatment response rates; [47] and cost parameters. [49] 6.…”
Section: Health Economic Results In Established Ramentioning
confidence: 99%
“…Contrastingly, for patients on cDMARDs or palliative care the HAQ score was assumed to increase linearly at a rate of 0.045 and 0.06 per year respectively. Changes in EQ-5D were estimated following a linear mapping algorithm from changes in HAQ scores reported by Brennan et al [38]. Mortality was assumed to be affected by HAQ score, with a hazard ratio of 1.43 per HAQ score point applied following Norton et al [39] Unit costs were taken from the Personal Social Services Research Unit,[40] British National Formulary (BNF), [41] and NHS Reference Costs.…”
Section: Cost-effectiveness Evidence Provided By the Companymentioning
confidence: 99%